The Relationship Between Education Level, Income Figures and Sports Preferences: A Perspective on the Cost of Exercise and Physical Fitness - Irfan, Mohammad (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2024)
Education, income and sports preferences are indispensable needs for all humans. With education, income and sports preferences will certainly improve physical and spiritual health in humans. This study aims to determine the relationship between education level, income and sports preferences from the perspective of sports and physical fitness costs. This type of research is a type of correlation research to find out the relationship between variables. The population in this study is 276 and the basis for sampling in this study, the researcher uses purposive sampling, so that the sample in this study is 173 subjects. The data collection instrument in this study uses a questionnaire that has been validated by experts with a validity value of 0.87 and a reliability of 0.84. The data analysis technique in this study uses quantitative descriptive analysis with hypothesis testing analysis carried out in a gradual manner as a condition for standardized regression after which the model is refined. There are 4 hypothesis tests, namely: major hypothesis testing 1, minor hypothesis testing is divided into 3, hypothesis 1, hypothesis 2 and hypothesis 3. The results of this study are that there is a significant relationship at the level of education, income and sports preferences reviewed from the perspective of sports and physical fitness costs by being marked by the value of each variable, namely sig. (2-tailed) 0.000. Based on the nature of the correlation, it can be concluded that there is a significant relationship at the level of education, income and sports preferences reviewed from the perspective of sports and physical fitness costs. So the implication of this research is the importance of instilling a healthy soul, both physically and spiritually healthy. Physical activity is not expensive, depending on how we have the motivation to keep exercising.